What characterizes a good RESULTS section? Relationship between quality and linguistic-discursive features in Computer Engineering Final Degree Project - Lillo Fuentes, Fernando; López-Ferrero, Carmen; Venegas, René (Círculo de Lingüística Aplicada a la Comunicación, 2023)
The present study aims to link linguistic-discursive features with quality (LDQ) in the RESULTS section of Final Degree Project (TFG) in Computer Engineering. For this purpose, we measured, with the support of computational tools, 24 features that have been commonly related to CLD, in addition to others that we included from interviews conducted with members of the disciplinary community. It is observed that the quality of the section is mainly attributed to: a) the communicative purposes linked to the macro-purpose of the section, b) the relationship between the written text and multimodal artifacts, c) textual cohesion, d) syntactic complexity and e) the length of the writing (words number). Based on the above, we argue that to determine the CLD of the section, with the support of computer tools, the characteristics of the discursive genre, the formal aspects, the content of the text and the community’s own conventions should be taken into account. Our findings can be very useful for the creation of didactic material that supports the writing of this complex section and for the determination of the features to be included in computer tools that automatically evaluate CLD, since all of them have been operationalized with the support of computers.
Keywords: Final Degree Project; Discourse in Engineering; Linguistic-discursive quality; Results section